Interactive 3D Virtual Tour for Wedding Set Visualization on Android-Based E-Catalog - Irma Wulandari; Aji Sapta Pramulen; Muhammad Haykal Abdillah; Jauari Akhmad Nur Hasim; Fardani Annisa Damastuti; Ibrohim Yofid Fananda (Fakultas Teknik Universitas Muria Kudus, 2026)
The digital transformation of the wedding industry encourages Wedding Organizer (WO) businesses to innovate in service presentation. This study develops a Virtual Wedding Set Visualization application as an Android-based e-catalog platform with a 3D virtual tour concept for wedding decoration services. The application is intended to overcome the limitations of conventional promotional methods, which often lack interactivity and fail to provide realistic decoration visualizations. The development process adopts the Multimedia Development Life Cycle (MDLC) method, covering the stages of concept, design, material collection, assembly, and testing. Three-dimensional assets were modeled based on actual decorations from the business partner tigasatu.decoration and integrated into the application using Unreal Engine. System testing was conducted through BlackBox and Functional Testing, both of which confirmed that all features functioned correctly. Furthermore, feasibility testing with 28 respondents demonstrated a high level of satisfaction with the application's visual presentation, ease of navigation, and effectiveness as a digital promotional tool. These results indicate that the application successfully enhances the interaction between WOs and prospective clients, while contributing an innovative approach to the adoption of interactive multimedia technology in the wedding service industry.